Expert Evaluation of the Organization of Physical Education in Educational Institutions with in the General Secondary Education System - Mykhailo Perehinets; Liudmyla Dolzhenko (Lesya Ukrainka Volyn National University, 2017)
The current relevance of the research is due to a decrease and sometimes lack of motivation in students, especially high school age, to exercise so as the time limit for extracurricular forms of organization of physical education. The goal of the study was to determine the opinions of teachers of physical culture, on the organization of physical education in educational institutions of secondary education. The results of the research paper present data obtained from the survey author Physical Education teachers working in various schools of secondary education in Ivano-Frankivsk, on the organization of physical education in school. The research found that 21,2 % of teachers still do not take into account the views of students in choosing the variant modules. Identified guidance to teachers introduced new variant modules of the program of physical education. Described list of diseases that are ill students and other features of the educational process with physical training. The findings obtained in the study provide an opportunity to «look through the eyes of teachers» in the process of physical education in schools of general secondary education, recommendations for improving curriculum. The material can serve as methodical teacher to develop planning documents for schoolboy of all ages. The actual survey allows luggage improve teacher of physical culture in school.